KUALITAS PELAYANAN PUBLIK SECARA ELEKTRONIK DALAM PELAKSANAAN SISTEM ONLINE SINGLE SUBMISSION: (Studi pada Dinas Penanaman Modal Provinsi Sulawesi Selatan) - alifa rezky utami anwar (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2022)
Public service reform can be marked by the quality and renewal of services provided to the community, in this case the South Sulawesi Province Investment Service has carried out updates through licensing services by issuing an Online Single Submission system which aims to provide convenience for the community in obtaining business licenses as business legality. The type of research used is a qualitative method with a descriptive approach. The results of the study show that the services provided to the community have been carried out in accordance with the applicable SOPs, however, because this system is still being updated, there are still some obstacles found in the field, one of which is related to technical problems in the use of the Online Single Submission system that occurs in sectors or the Standard Classification of Indonesian Business Fields. (KBLI) was not found or was not aligned between sectors and KBLI, even though this system is still new but there have also been successes that have been achieved such as an increase in MSME growth in South Sulawesi which occurred in 2019 - 2021.